Exploring the mechanisms of action of human secretory RNase 3 and RNase 7 against Candida albicans. Issue 5 (8th June 2016) - Salazar, Vivian A.; Arranz‐Trullén, Javier; Navarro, Susanna; Blanco, Jose A.; Sánchez, Daniel; Moussaoui, Mohammed; Boix, Ester
Abstract : Human RNases 3 and 7 are wide‐spectrum host defense antimicrobial proteins. We have chosen here a eukaryotic pathogen to study their mechanism of action. Comparison of wild‐type proteins versus active site and cell binding mutants on yeast cultures revealed a dual role. Contribution of enzymatic activity to the RNases antifungal properties envisages cellular RNA targeting as an effective strategy for antibiotic design. Abstract: Human antimicrobial RNases, which belong to the vertebrate RNase A superfamily and are secreted upon infection, display a wide spectrum of antipathogen activities. In this work, we examined the antifungal activity of the eosinophil RNase 3 and the skin‐derived RNase 7, two proteins expressed by innate cell types that are directly involved in the host defense against fungal infection. Candida albicans has been selected as a suitable working model for testing RNase activities toward a eukaryotic pathogen. We explored the distinct levels of action of both RNases on yeast by combining cell viability and membrane model assays together with protein labeling and confocal microscopy. Site‐directed mutagenesis was applied to ablate either the protein active site or the key anchoring region for cell binding. This is the first integrated study that highlights the RNases' dual mechanism of action. Along with an overall membrane‐destabilization process, the RNases could internalize and target cellular RNA. The data support the contribution of the enzymatic activity for the antipathogen action of both antimicrobial proteins, which can be envisaged as suitable templates for the development of novel antifungal drugs. We suggest that both human RNases work as multitasking antimicrobial proteins that provide a first line immune barrier.